Africa cannot achieve the Malabo Declaration commitments: Statistical impossibility or logical fallacy - Benin, Samuel (International Food Policy Research Institute, 2024)
The results of the recently released Comprehensive Africa Agriculture Development Programme (CAADP) 4th Biennial Review (BR) report indicate that Africa’s performance in 2023 toward achieving the Malabo Declaration commitments by 2025 has strayed farther away from being on-track. Using a scorecard method to review progress in 58 indicators that represent the commitments, previous BR reports show that the number of countries assessed to be on-track to achieve the commitments has dwindled over time, from twenty in 2017 to four in 2019 and only one in 2021. In the 4th BR in 2023, none of the 49 participating countries was on on-track. This seems to conflict with evidence of positive trends in other continent-level reports on related development indicators. According to the African Economic Outlook for example, the contribution of agriculture to overall economic growth in Africa has remained stable, especially as growth in the services and industry sectors has been irregular—and even negative in 2020 due to the COVID-19 pandemic. The latest editions of the Africa Agriculture Trade Monitor, Africa Agriculture Status Report, and Annual Trends and Outlook Report5 also show substantial progress in terms of expansion of agricultural investments, trade, and growth and improvement in poverty and nutrition outcomes, amid challenges associated with the pandemic, climate change, conflicts, and epidemics such as the locust and fall armyworm infestations. The BR scoring method and data have some issues that contribute to the seemingly worsening performance.